2016
DOI: 10.1080/1744666x.2016.1201423
|View full text |Cite
|
Sign up to set email alerts
|

Crosstalk between skin inflammation and adipose tissue-derived products: pathogenic evidence linking psoriasis to increased adiposity

Abstract: Psoriasis is a chronic skin disorder associated with several comorbid conditions. In psoriasis pathogenesis, the role of some cytokines, including TNF-α and IL-17, has been elucidated. Beside their pro-inflammatory activity, they may also affect glucose and lipid metabolism, possibly promoting insulin resistance and obesity. On the other hand, adipose tissue, secreting adipokines such as chemerin, visfatin, leptin, and adiponectin, not only regulates glucose and lipid metabolism, and endothelial cell function … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
66
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(70 citation statements)
references
References 123 publications
3
66
0
1
Order By: Relevance
“…Elevated serum concentration of leptin has been found in patients with cardiovascular risk factors and obesity status [15]. It has been suggested that leptin may be a marker of severity of psoriasis [20].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Elevated serum concentration of leptin has been found in patients with cardiovascular risk factors and obesity status [15]. It has been suggested that leptin may be a marker of severity of psoriasis [20].…”
Section: Discussionmentioning
confidence: 99%
“…It activates monocytes and macrophages to produce proinflammatory IL-6 and TNF- α . Leptin also enhances the production of proinflammatory Th1 cytokines and suppresses the production of anti-inflammatory Th2 cytokines at the same time [15]. Resistin is another adipocyte-specific proinflammatory polypeptide synthesized mostly by macrophages and monocytes contained in fat tissue.…”
Section: Introductionmentioning
confidence: 99%
“…Particularly patients with severe psoriasis and psoriatic arthritis have an increased risk of cardiovascular mortality that is independent of traditional cardiovascular risk factors [2, 23]. The release of inflammatory molecules and cytokines in psoriasis may play an important role in this association [9]. Psoriasis predispose to metabolic disturbances, and on the other hand obesity can worsen the skin inflammation in psoriasis.…”
Section: Introductionmentioning
confidence: 99%
“…These findings were consistent with some studies published recently [28] Guler et al that found the same results. In fact, leptin was mainly secreted by adipocytes and target the cells directly, such as epithelial cells, nervous cells, and immune cells (T helper), by expressing its receptor (LEPR) which lead to the first steps of pathological pathway of many inflammatory diseases [29].…”
Section: Discussionmentioning
confidence: 99%